Domestic Violence - An Old Malady with a New Perspective (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Domestic violence is one of the most common types of violence that occurs behind closed doors and sometimes in public. The innate desire of humans to control and have power over others results in practising this control over their near and dear ones. Domestic violence is considered to have occurred when one intimate partner uses physical violence, coercion, threats, intimidation, isolation and/or emotional, sexual and economic abuses over the other to maintain power and control. Other names of domestic violence include, partner violence, relationship violence, intimate partner abuse, spouse abuse, domestic abuse, wife abuse or wife beating and battering. It encompasses violence against both men and women and includes gay and lesbian relationships. It has a widespread prevalence across all countries, irrespective of social, economic, religious or cultural division. Women are generally the sufferers/ victims of abuse, as from olden times the socio-cultural environment is so inclined towards patriarchy and masculinity that they justify wife beating as a part of male supremacy.
Keywords: Domestic; Intimate partners; Power; Widespread; Violence; Law